Inflammatory Biomarkers Predict Heart Failure Severity and Prognosis in Patients With Heart Failure With Preserved Ejection Fraction: A Holistic Proteomic Approach - Hage, Camilla; Michaëlsson, Erik; Linde, Cecilia; Donal, Erwan; Daubert, Jean-Claude; Gan, Li-Ming; Lund, Lars H. (Circulation. Cardiovascular genetics, 2017)
BACKGROUND—Underlying mechanisms in heart failure (HF) with preserved ejection fraction remain unknown. We investigated cardiovascular plasma biomarkers in HF with preserved ejection fraction and their correlation to diastolic dysfunction, functional class, pathophysiological processes, and prognosis. METHODS AND RESULTS—In 86 stable patients with HF and EF ≥45% in the Karolinska Rennes (KaRen) biomarker substudy, biomarkers were quantified by a multiplex immunoassay. Orthogonal projection to latent structures by partial least square analysis was performed on 87 biomarkers and 240 clinical variables, ranking biomarkers associated with New York Heart Association (NYHA) Functional class and the composite outcome (all-cause mortality and HF hospitalization). Biomarkers significantly correlated with outcome were analyzed by multivariable Cox regression and correlations with echocardiographic measurements performed. The orthogonal partial least square outcome-predicting biomarker pattern was run against the Ingenuity Pathway Analysis (IPA) database, containing annotated data from the public domain. The orthogonal partial least square analyses identified 32 biomarkers correlated with NYHA class and 28 predicting outcomes. Among outcome-predicting biomarkers, growth/differentiation factor-15 was the strongest and an additional 7 were also significant in Cox regression analyses when adjusted for age, sex, and N-terminal probrain natriuretic peptideadrenomedullin (hazard ratio per log increase 2.53), agouti-related protein; (1.48), chitinase-3–like protein 1 (1.35), C–C motif chemokine 20 (1.35), fatty acid–binding protein (1.33), tumor necrosis factor receptor 1 (2.29), and TNF-related apoptosis-inducing ligand (0.34). Twenty-three of them correlated with diastolic dysfunction (E/e′) and 5 with left atrial volume index. The IPA suggested that increased inflammation, immune activation with decreased necrosis and apoptosis preceded poor outcome. CONCLUSIONS—In HF with preserved ejection fraction, novel biomarkers of inflammation predict HF severity and prognosis that may complement or even outperform traditional markers, such as N-terminal probrain natriuretic peptide. These findings lend support to a hypothesis implicating global systemic inflammation in HF with preserved ejection fraction. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov; Unique identifierNCT00774709.